Rancang Bangun Alat Deteksi Kebakaran Otomatis Berbasis Internet Of Thing Dan Wireless Di Dapur Rumah Makan Soponyono - Muhamad Arrafi (Jurnal Sains Informatika Terapan, 2025)
This research aims to design and implement an automatic fire detection device based on Internet of Things (IoT) and wireless technology, applied in the kitchen of Rumah Makan Soponyono. The system is developed to detect fire and smoke early using a flame sensor and an MQ-2 gas sensor connected to an ESP8266 microcontroller as the main controller. Sensor data are processed by the microcontroller and transmitted via the internet in the form of real-time notifications through the Telegram application. This allows the restaurant owner to receive immediate alerts even when not on-site. The prototype also includes a buzzer, LED, and 16x2 LCD as local warning indicators. The experimental results show that the system can detect fire at a distance of 20 cm and smoke at 3 cm, with a response time of less than two seconds. Once fire or smoke is detected, the system automatically sends notifications to Telegram and activates the local alarm. This IoT-based system provides an effective solution to enhance kitchen safety, minimize fire risks, and contribute to the application of IoT technology in early warning and fire prevention systems.